The Effect of Using Embankments and Modifying of Stepped Seawall Slope as Alternatives to Reduce over Topping at Selatbaru Beach Bengkalis - Zulkarnain, Zulkarnain; Febriani, Oni; Lizar, Lizar (Politeknik Negeri Bengkalis, 2024)
Located in Selatbaru Village, about 25 km from the centre of Bengkalis City, Selatbaru beach has become afavourite destination for tourists who want to enjoy the beauty of nature while engaging in outdoor activities. At thatbeach, a stepped-type seawall has been constructed to prevent erosion and make it easier for visitors to enjoy the beach,such as going down to and coming up from the beach. The current situation is during high tide and strong winds, wavesrun up the top of the seawall, causing seawater to surge onto the land. This research will conduct experiments by creatinga prototype based on field survey data and laboratory scale, including the seawall dimensions, water level, and waveheight, with a scale ratio of 1:10. The experimental scenarios to be conducted in the laboratory a. Existing seawall slopeof 1:3 with embankment, b. Changing the seawall slope to 1:5, and c. Changing the seawall slope to 1:5 withembankment. The irregular wave height to be simulated in the laboratory is 0.8 meters. The experiment will be conductedto observe the response of the seawall structure to incoming waves and the over topping occurring on the seawallstructure. The results shows that the alternative of adding an embankment and using a 1:3 seawall slope, has already beenable to reduce over topping volume 40,74 %. For the second scenario, the over topping volume decreased by 77.78 %,while the third scenario reduced over topping by 100 %. The best scenario is the third with slope to 1:5 and added of embankment that will decrease volume overtopping up to 100 %.